2019
DOI: 10.1021/acsami.9b08107
|View full text |Cite
|
Sign up to set email alerts
|

Difluoroboron-Enabled Thermally Activated Delayed Fluorescence

Abstract: A new series of tetracoordinated boron-enabled thermally activated delayed fluorescence (TADF) materials with a donor–acceptor BF2-type framework were designed and conveniently synthesized. Difluoroboron plays a critical role and acts as a key to coordinate with the latent acceptor of the 2-(4-phenylpyridin-2-yl)­phenol (PPyPOH) moiety to realize TADF. TADF materials are air-stable and have a high photoluminescence quantum yield of up to 99%. NOBF2-Cz- and NOBF2-DPCz-doped blue OLEDs demonstrated EQEs of 11.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…In 2019, Li's group developed four green TADF materials (NOBF2-Cz, NOBF2-DTCz, NOBF2-DPCz, and NOBF2-DMAC) based on difluoroboron acceptors (Figure 11). [63] When increasing the electron-donating strength of donors, the HOMO energy level would decrease, causing the reduced energy gap and a green emission in NOBF2-DMAC (542 nm). The result indicates that the emission wavelength can be adjusted by introducing donors with different electron-donating ability.…”
Section: The Tadf Molecules With Green Emissionmentioning
confidence: 99%
“…In 2019, Li's group developed four green TADF materials (NOBF2-Cz, NOBF2-DTCz, NOBF2-DPCz, and NOBF2-DMAC) based on difluoroboron acceptors (Figure 11). [63] When increasing the electron-donating strength of donors, the HOMO energy level would decrease, causing the reduced energy gap and a green emission in NOBF2-DMAC (542 nm). The result indicates that the emission wavelength can be adjusted by introducing donors with different electron-donating ability.…”
Section: The Tadf Molecules With Green Emissionmentioning
confidence: 99%
“…However, the half-lifetime at a constant driving current density of 10 mA/cm 2 reached to 2,354 h. They demonstrated the first trial of design and synthesis of four-coordinate boron and tridentate dppy ligand-based blue TADF emitters. Later, Li G. et al (2019) reported a new series of tetracoordinated blue TADF emitters using donor-acceptor BF2-type skeleton. Tetracoordinated difluoroboron molecules are air-stable, and they can enhance the molecular rigidity to have a high PLQY.…”
Section: Partially Bridged Boron-type Acceptor For Blue Thermally Actmentioning
confidence: 99%
“…Almost simultaneously, another series of ESIPT‐blocked BF 2 complexes was reported as efficient and stable TADF emitters in OLEDs. [ 117 ] Despite their high PLQY values (65% to 99%), these compounds show moderate EQE values (11% to 15.8%) in the blue‐green region due to their comparatively large Δ E ST values (0.08 to 0.22 eV). Importantly, lifetime studies of NOBF 2 ‐DPCz‐ and NOBF 2 ‐DMAc‐doped OLEDs exhibited long operational lifetimes of 54 and 920 h at 50% of their initial luminescence at 500 cd m −2 , respectively.…”
Section: Four‐coordinate Boron‐based Tadf Emittersmentioning
confidence: 99%